Association Between Chemosensory Dysfunction and Diet Quality in United States Adults. Issue 1 (January 2022) - Roxbury, Christopher R.; Bernstein, Isaac A.; Lin, Sandra Y.; Rowan, Nicholas R.
Background: Evidence suggests chemosensory dysfunction (CSD) patients have altered diet, but population-level evidence assessing diet quality in CSD patients is lacking. Objective: We examined the association between CSD and diet quality in a representative sample of United States adults. Methods: This cross-sectional study included 2831 adults aged greater than 40 years from the 2013-2014 National Health and Nutrition Examination Survey who completed the taste/smell questionnaire and examination. Mean nutrient intake in subjects with self-reported olfactory/gustatory dysfunction (sOD/sGD) and measured olfactory/gustatory dysfunction (mOD/mGD) were compared to those without CSD using univariate Wilcoxon rank-sum tests. The Healthy Eating Index (HEI), a validated measure of diet quality, was calculated. The proportion of subjects with CSD with bottom-quartile HEI was compared to those without CSD using multivariate logistic regression, adjusting for demographic and socioeconomic covariates. Results: The population-weighted prevalence of sOD, sGD, mOD, and mGD was 20.1%, 14.4%, 15.9% and 25.6%, respectively. Subjects with mOD had lower mean intake of total calories, total fat, protein, sodium, and potassium compared to normal subjects (1873.4 ± 49.6 vs 2010.2 ± 24.2 kcal, 72.3 ± 2.7 vs 78.6 ± 1.0 gm, 74.0 ± 2.5 vs 80.4 ± 0.6 gm, 3122 ± 97.2 vs 3353.2 ± 37.0 mg, 2509.8 ± 69.8 vs 2684.7 ± 26.1 mg, P  < 0.05 respectively). When controlling for sociodemographic factors and comorbidities, subjects with sOD were more likely to have bottom-quartile HEI compared to normal subjects (OR 1.33, 95% CI 1.04–1.70). Conclusions: This population-level study suggests an association between poor diet quality and variation in dietary intake in patients with CSD, which warrants further investigation and suggests the possible need for nutritional counseling for CSD patients.